The Influence Of Organizational Culture, Work Environment And Work Motivation Towards The Lecturers’ Performance At Pancasetia Economic College In Banjarmasin, South Kalimantan - Fredy Jayen; Abdul Kadir; Asruni (Archives of Business Research, 2022)
This study aims to analyze the influence of organizational culture, work environment and work motivation on the performance of lecturers at the Pancasetia School of Economics Banjarmasin. The population in this study were all permanent lecturers who had NIDN as many as 135 people. With the sampling technique using the purposive sampling method, the selected sample was 80 lecturers. this type of research method uses the correlational method where this study compares and determines the relationship between organizational culture, work environment and work motivation variables with the performance of lecturers at the Pancasetia School of Economics Banjarmasin. Analysis of the data in this study using multiple linear regression analysis, while testing the hypothesis using the F test, R2, and t test. The results showed that simultaneously and partially organizational culture, work environment and work motivation had a significant effect on the performance of lecturers at the Pancasetia School of Economics Banjarmasin. The organizational culture variable has the most dominant influence compared to the work environment and work motivation variables.